Investigation of Electroacupuncture and Manual Acupuncture on Carnitine and Glutathione in Muscle - Toda, Shizuo (Hindawi Publishing Corporation, 2011)
Electroacupuncture (EA) and manual acupuncture (MA) have therapeutic effects on muscle fatigue in muscle disease. The deficiencies of carnitine and glutathione induce muscle fatigue. This report investigated the effects of EA and MA on carnitine and glutathione in muscle. After the mice of EA group were fixed in the animal cage, right Zusanli (ST36) and Jiexi (ST41) were acupunctured and stimulated with uniform reinforcing and reducing method by twirling the acupuncture needle for 15 min. And then, the needle handles were connected to an electric stimulator for stimulating the acupoint with dense-sparse waves. After the mice of MA group were fixed in an animal cage, right ST36 and ST41 were acupunctured and allowed for 15 min. The mice of normal control group were not acupunctured and stimulated for 15 min. The mice of all groups were killed for collecting muscle tissue 1 h after the final treatment. Carnitine and glutathione in homogenate of muscle tissue were determined with carnitine (Kainos Laboratories Co., Tokyo, Japan) and glutathione assay kit (Dojin Chemicals Co., Kumamoto, Japan). Carnitine level in muscle tissue of MA group was significantly higher than those of EA group and normal control group. Carnitine level in muscle tissue of EA group was not significantly different from that of normal control group. Glutathione levels in muscle tissue of EA group and MA group were significantly higher than that of normal control group. This report presented that carnitine in muscle is increased by MA, and not increased by EA, and that glutathione in muscle is increased by EA and MA.